ANALISIS POTENSI EKONOMI DAN STRATEGI PEMBANGUNAN EKONOMI DI BOGOR BARAT - Marfiani, Teni; Hartoyo, Sri; Manuwoto, Manuwoto (Program Studi Manajemen Pembangunan Daerah. Fakultas Ekonomi dan Manajemen. IPB University, 2009)
The purpose of this study is to analyze the readiness of the potential economy at the developmental areas in West Bogor and to formulate a developmental economy strategy to actualize in the implementation of autonomy development. In general, the result showed that the western region of Bogor has an economic potential that can be developed, therefore it can be made as one of the main factors in the recommendation to become an autonomous district. Western Bogor region has a few growth centers to draw the growth of the region. Growth and service centers are still accumulating in urban areas resulting in a gap caused by the intensity of linkages between urban areas and rural areas in which are relatively limited.The selected strategy priorities are: (1) the development of industries that support the agricultural aspect (agro-industry) as an effort to optimize the utilization and managingsustainable natural resources by utilizing the potentials Bogor Regency has (economic conditions, government policies Bogor Regency, geographical location) as well as cooperation with private sector / other, (2) Finding and promoting the image of commodity and regional superior products that provide value-added (GDP and PAD) for the local community using the criteria of potential value-added direct a commodity / product for poor families, and (3) creating a conducive business climate to support local capacity building by expanding the local tax base and expand the productive sectors of the economy of the people.Implications of policy directed as social, cultural, political, institutional, or spatial aspects of the development budget and policy. Furthermore, the basic sector analysis should be done at sub-district unit so that it can be seen a leading sector per district based on income (GDP) per district.Keywords: Growth and service centers, local economic potential, regional development.